Altered neuromagnetic activity in default mode network in childhood absence epilepsy - Wang, Yingfan; Li, Yihan; Sun, Fangling; Xu, Yue; Xu, Fengyuan; Wang, Siyi; Wang, Xiaoshan (Frontiers in Neuroscience, 2023)
Purpose: There are numerous potential biomarkers of epileptogenesis, however, biomarker research based on magnetoencephalography (MEG) is relatively lacking. In this study, we compared neuromagnetic activity in the default mode network (DMN) between children with childhood absence epilepsy (CAE) and healthy controls to explore the potential of MEG to identify CAE during interictal periods. Methods: Using a cross-sectional design, we analyzed MEG data from children newly diagnosed with CAE and controls matched for age and sex. The spectral power and functional connectivity of the DMN were estimated using minimum norm estimation combined with the Welch technique and corrected amplitude envelope correlation. Results: Characteristic interictal neuromagnetic activity was observed in the DMN of CAE patients. Compared with controls, the relative spectral power of DMN regions (except bilateral precuneus) in CAE children was significantly increased in the delta band (pcorrected < 0.01), whereas the values of all DMN regions in the beta-gamma 2 band were significantly decreased (pcorrected < 0.01). In terms of functional connectivity, the node strength of DMN regions in CAE children was significantly increased in each frequency band, especially the right medial frontal cortex in the beta band (Controls: 0.1510 vs Interictal: 3.527, pcorrected < 0.01). Comparing relative node strength between groups, the right precuneus in CAE children decreased significantly (β：Controls:0.1009 vs CAE:0.0475; γ 1：Controls:0.1149 vs CAE:0.0587, pcorrected < 0.01) such that it was no longer the central hub. Conclusion: CAE patients show unique oscillatory activity patterns and functional connectivity characteristics of the DMN during interictal periods. This unique neuromagnetic activity is of great value for early recognition of CAE patients and scientific understanding of absence seizures.